Kinetics Photodegradation of Methylene Blue Dye Using ZnO-Montmorillonite Composite - Putri, Suriati Eka; Pratiwi, Diana Eka; Ria, Tiara Anugrah (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2025)
The purpose of this study was to determine the degradation kinetics of methylene blue dyes using ZnO-Montmorillonite (MMT) composites. This study is an experimental research covering several stages, namely the preparation and purification of MMT samples, the synthesis of ZnO-MMT composites by impregnation method, the characterization of ZnO-MMT composites, and the determination of optimal conditions for the degradation of methylene blue (MB) dyes using the UV-Vis instrument. The results of the ZnO-MMT composite research were able to degrade MB dyes irradiated by UV light with an optimal time of 150 minutes with a photodegradation rate of 4.199 minutes-1.Keywords: Kinetics, Reaction Rate, Photodegradation, MB Dye, ZnO-MMT.